Treatment of postinfectious irritable bowel syndrome and noninfective irritable bowel syndrome with mesalazine - Bafutto,Mauro (2011)
CONTEXT: Recent studies support the hypothesis that postinfectious irritable bowel syndrome and some irritable bowel syndrome patients display persistent signs of minor mucosal inflammation. Mesalazine has intestinal anti-inflammatory properties including cyclooxygenase and prostaglandin inhibition. The effects of mesalazine on postinfectious irritable bowel syndrome and noninfective irritable bowel syndrome patients are still unknown. OBJECTIVE: To observe the effects of mesalazine on postinfectious irritable bowel syndrome and noninfective irritable bowel syndrome with diarrhea patients. METHODS: Based on Rome III criteria, 61 irritable bowel syndrome with diarrhea patients (18 years old or more) were included in the evaluation. Patients were divided into two groups: postinfectious irritable bowel syndrome group, with 18 patients medicated with mesalazine 800 mg 3 times a day for 30 days; noninfective irritable bowel syndrome group, with 43 patients medicated with mesalazine 800 mg 3 times a day for 30 days. Symptom evaluations at baseline and after treatment were performed by means of a four-point Likert scale including stool frequency, stool form and consistency (Bristol Stool Scale), abdominal pain and distension (maximum score: 16; minimum score: 4). RESULTS: Postinfectious irritable bowel syndrome group presented a statistically significant reduction of the total symptom score (P<0.0001). The stool frequency was significantly reduced (P<0.0001), and stool consistency, improved (P<0.0001). Abdominal pain (P<0.0001) and abdominal distension were significantly reduced (P<0.0001). Noninfective irritable bowel syndrome group presented a statistically significant reduction of total symptom score (P<0.0001). Also, the stool frequency was significantly reduced (P<0.0001) and stool consistency, improved (P<0.0001). Abdominal pain (P<0.0001) and abdominal distention were significantly reduced (P<0.0001). There was no statistical difference between postinfectious irritable bowel syndrome group and noninfective irritable bowel syndrome group on total symptom score results at 30th day of therapy with mesalazine 800 mg 3 times a day. (P = 0.13). CONCLUSION: Mesalazine reduced key symptoms of postinfectious irritable bowel syndrome and noninfective irritable bowel syndrome with diarrhea patients.